FENOMENA LAPAK MESUM Di KAWASAN WISATA GRONGGONG KABUPATEN CIREBON SEBAGAI TEMPAT PERGAULAN BEBAS Di KALANGAN REMAJA. - Yeni Wahyuni * (Pendidikan Sosiologi FIS UNY, 2012)
Behavior promiscuity now this can be done by anyone, anytime and anywhere, including the one in the area of tourism. In tourist areas often appeared behavioral Gronggong promiscuity among teenagers. This study aims to: 1). Describe the factors that cause a nasty stall in the area of tourism can be a region Gronggong promiscuity among teenagers, 2). The effort to control local government officials in tourism mentertibkan Gronggong of behavior promiscuity among teenagers.This study uses qualitative research methods with the primary data sourceconsists of the visitors, the traders in the Area Tourism Gronggong, PP Satpol Cirebon District, the Village Head Patapan Cirebon, Cirebon District Head of Tourism, andCommunities around Gronggong tourist area, while for source secondary data obtainedthrough documentation, literature study using books, and print media. Data collection techniques used include observation, interviews, and documentation. The subjects inthis study were the visitors and the traders in the tourist areas Gronggong with 4 stalltraders. The technical validity of the data in this study using the technique oftriangulation of sources and methods. In the data analysis techniques using the interactive analysis of Miles and Huberman.The results obtained are the factors that cause a nasty stall in the area of tourism can be a region Gronggong promiscuity among teenagers consists of: 1). Nonphysical factors consist of building construction shanties. Shanties located on the left path has an insulated building, located there under (the category is not visible), stall located on the right road in the form of benches scattered, and many benches that are built on a hill standing upright. The lack of lighting (illumination). While physicalfactors consist of a dynamic social relations between traders and visitors Gronggong tourist area, and factors of social control of local government officials are less than optimal. 2). The effort to control local government officials in tourism mentertibkan Gronggong of promiscuity behaviors among adolescents such as by recording the location then the insulated, provide guidance, socialization, and in its supervision on patrol every single week, right the situation is done at a certain time and depending on the needs , as before the religious holidays, and towards the end of the year.Keywords: Phenomenon bawdy shanties, adolescents, and control